Correlación entre los niveles séricos de factor de crecimiento insulinoide tipo I (IGF-I) con el estadio de maduración esquelética (2005)
ABSTRACT: In order to detect indicators of the onset of the spurt of puberal growth, the IGF-I seric levels were correlated with the age, weight, height, skeletal maturity stage (Hägg and Taranger). Each of the variables were correlated; other variables were included in the study such as general development and sexual maturity (Tanner and, Prader). A total of 33 patients were studied: 18 male and 15 female, between 8 and 12 years. Healthy children in Tanner I sexual maturity stage was the research criterion for inclusion. Blood samples, hand wrist roentgenograms, and general development data were taken every six months during the course of three years (2000- 2002). The general population, mestizo, was 9.48 ± 0.65 years old average, it was in 25-50 percentile range for weight (29.17 ± 6.41 kg) and height (131.50 ± 6.91 cm). At the beginning of the study, the population was in Tanner I sexual maturity stage. There was no sexual difference, with respect to the IGF-I seric level concentration (175 ± 77.06 in boys, and 175.80 ± 88.39 in girls), even though, statistically significant correlations were found in females, between IGF-I and age (r = 0.56, p = 0.031), IGF-I and weight (r = 0.58, p = 0.023). In the boys and the girls, statistically significant correlations were found between age and weight, age and height and height and weight. In males, the right and left testis volumes showed statistically significant correlations with weight (r = 0.60, p = 0.009; r = 0.55, p = 0.017), and with height (r = 0.53, p = 0.023; r = 0.51, p= 0.030 ).